Advance of transforming growth factor beta in traumatic brain injury. Issue 1 (28th March 2015) - Lu, Fan; Xu, Yang; Wang, Ting‐Hua
Abstract : Transforming growth factor beta (TGF‐β) is a multifunctional cytokine whose neural functions are increasingly recognized. The machinery of TGF‐β signaling, including the serine kinase type transmembrane receptors, is present in the central nervous system. Indeed, TGF‐β expression is induced following the brain tissue injury. This review will describe the role of TGF‐β after traumatic brain injury, including anti‐inflammatory, actions as well as the promotion of scar formation and neuroregeneration.